2012
DOI: 10.1161/circulationaha.111.051540
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Capillary Wedge Pressure Augments Right Ventricular Pulsatile Loading

Abstract: Background Right ventricular (RV) failure from increased pulmonary vascular loading is a major cause of morbidity and mortality, yet its modulation by disease remains poorly understood. We tested the hypotheses that, unlike the systemic circulation, pulmonary vascular resistance (RPA) and compliance (CPA) are consistently and inversely related regardless of age, pulmonary hypertension (PH), or interstitial fibrosis, and that this relation may be changed by elevated pulmonary capillary wedge pressure (PCWP), au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
335
6
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 396 publications
(370 citation statements)
references
References 19 publications
27
335
6
2
Order By: Relevance
“…This observation provides further physiological support for the role of exogenous administration of sodium nitrite for nonGroup 1 PH patients. Tedford et al demonstrated that elevated pulmonary capillary wedge pressure was associated with lower Cpa for any given PVR (shifting the resistance-compliance curve down and to the left), although there is still some debate about this in the literature (25,32). We found no difference in the baseline resistance-compliance relationship between patient groups.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This observation provides further physiological support for the role of exogenous administration of sodium nitrite for nonGroup 1 PH patients. Tedford et al demonstrated that elevated pulmonary capillary wedge pressure was associated with lower Cpa for any given PVR (shifting the resistance-compliance curve down and to the left), although there is still some debate about this in the literature (25,32). We found no difference in the baseline resistance-compliance relationship between patient groups.…”
Section: Discussioncontrasting
confidence: 55%
“…Treatment effects are presented as mean values and their 95% confidence intervals. Resistance-compliance curves were constructed and the data were fit to an inverse hyperbolic curve and compared using the extra sum-of-squares F test (Prism 6, GraphPad Software) (25). Statistical significance was defined as a 2-sided P value less than 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…24 Tedford et al have shown that increases in PCWP are associated with lower PA compliance at any given resistance, increasing the oscillatory load on the RV, and this effect occurs even acutely during exercise in patients with HFpEF. 78 Because they are connected in series, inadequate RV output could contribute to exercise limitation by promoting "underfilling" of the left heart during stress. Although this phenomenon has been demonstrated in HFrEF, 79 it has not been documented in patients with HFpEF.…”
Section: Vascular Stiffening and Dysfunctionmentioning
confidence: 99%
“…These main hemodynamic alterations expose the lung vasculature to pressure-induced challenges whose most immediate acute threat is pulmonary edema. 4 In the long term, the sustained backward hemodynamic transmission, along with the potential contribution of mitral insufficiency, increases the pulsatile loading on the right ventricle (RV) 5 and triggers pulmonary hypertension (PH) development and symptom exacerbation. 6 Thus, as a consequence of hemodynamic and functional perturbations, PH-HFpEF develops as a more advanced corollary of diastolic HF, leading to abnormal phenotypes of the lung microcirculation, 7,8 the arterial system, and right heart function 9-11 ( Figure 1).…”
mentioning
confidence: 99%